Rockburst hazard assessment and prevention and control strategies in the Ruihai gold mine - Li, Pengxiang; Wang, Zongwen; Chen, Bingrui; Peng, Jianping; Zhang, Bochao; Zhao, Jinshuai; Xie, Houlin (Frontiers in Earth Science, 2024)
Ruihai gold mine is a super large underwater gold mine with an initial mining depth of more than 1400 m.Deep mining may face rockburst disaster. In order to scientifically control the potential rockburst risk, ensure the safety of underground personnel and equipment, and realize the safe and efficient mining of the mine, it is necessary to evaluate the rockburst risk of the mine and formulate appropriate rockburst risk warning and mitigation strategies. XRD mineral composition analysis and conventional rock mechanical tests were carried out on the parent rock granite samples. The results show that there are differences in the lithologic composition and rock mechanics parameters of the three colors of granite, which are preliminarily determined as three kinds of granite; The rockburst tendency of three kinds of granites is evaluated by using three classical rockburst criteria, and the discrimination results of the three rockburst criteria are not completely consistent or even contradictory. The application limitations rockburst risk assessment based on index criteria are discussed and analyzed in detail. It is proposed to apply microseismic monitoring technology to warn and manage the rockburst risk of Ruihai gold mine in development and mining stages, and put forward microseismic monitoring layout schemes and targeted rockburst prevention and control measures in different stages. The research results can provide reference for similar projects.